Accountability of Regional Officials of Sidoarjo Regency In The Distribution of Groceries During The Covid-19 Pandemic - Akmal Maulana N. M.; Andre Purnairawan; Sholahuddin Al-Fatih; Jamil Jamil (Audito Comparative Law Journal (ACLJ), 2022)
This article aims to analyze the distribution of free groceries in the Sidoarjo regency during the Covid-19 pandemic. Free groceries program for citizens in almost every year by the local government. But it is slightly different in pandemic times like today, where the free Groceries program is more often done and on a large scale. One of them is carried out by the Sidoarjo Regency Government, East Java. Keep in mind that the thing that is affected by the outbreak of the Covid-19 Virus is an economic factor, which makes most people lose their eyes that make the weakening of the economic system in Indonesia no exception in Sidoarjo Regency itself. This paper takes socio-legal research to find out the problem of the distribution of free groceries in the Sidoarjo regency. The results of this study look at the extent of the accountability of the Sidoarjo Regency government with the Covid-19 outbreak in the community, namely from the start of the distribution of free food so that it is expected to provide more concrete results. Sidoarjo Regency government program is expected to be applied in the early stages of formulation, implementation, and evaluation of public policy.